GLUTATHION MENINGKATKAN KUALITAS TUBULUS SEMINIFERUS PADA MENCIT YANG MENERIMA PELATIHAN FISIK BERLEBIH - Laksmi, Desak Nyoman Indira (Buletin Veteriner Udayana; Vol 2 No. 1 Pebruari 2010)
The aims of this study was to find out influence of glutathione on tubuleseminiferous quality during the overtraining. This study was experimentally and randomlypretest-posttest with control group design. The samples of this study were strain Balb-Cadult male mice with the following criteria: body weight between 20-25 grams, age 2-3months, randomly, 48 mice were divided into two groups, 24 mice were control group andthe other 24 were treatment group (Po = physical overtraining group with aqua proinjection,intraperitoneal, and P1 = physical overtraining group with glutathione 6 Mmol/kg. BW/day, intra-peritoneal). Prior to the treatment, 12 mice were taken from each group forthe pre-test, by preparing microscopic preparation testicle and examination was performedto seminiferous tubules quality. The rests of the mice, 12 mice were used as for post-testexamination after 35 days treatment. The result showed that the quality of seminiferoustubules significantly increase (p<0, 05) after the glutathione treatment. It can be concludedthat the glutathione treatment improved the quality of seminiferous tubules.
Keywords: Physical overtraining, glutathione, seminiferous tubules quality